The Effectiveness of Quartet Card Game in Teaching Writing Descriptive Texts to Senior High School Students in Batu Ampar - Yuliani; Aunurrahman Aunurrahman; Maliqul Hafis (Proceedings of the International Conference on Literacy and Education, 2020)
This pre-experimental study aimed to find out the effectiveness of quartet card game in teaching writing descriptive text to the first-year students of a public senior high school in Batu Ampar in the Academic Year of 2018/2019. 36 first-year students were selected by using cluster random sampling. The researcher used writing test for data collection. The writing test sessions were conducted before (pre-test) and after (post-test) the treatment end. The researcher then conducted data analysis of the results of the tests by using inferential statistics, that is, by using t-test formula. The data analysis reveals that quartet card game is effective to teaching writing descriptive test. There is a significant difference of the result of the pre-test (mean score 59.17) and the result of the post-test (77.06) where the result of the t-test observed (16.961) is higher than the t-table (2.03).